α-Cationic Phosphines: from Curiosities to Powerful Ancillary Ligands - Rugen, Christian J.; Alcarazo, Manuel (Synlett, 2021)
The distinguishing feature of α-cationic phosphines is the presence of at least one substituent, normally (hetero)cyclic and positively charged, which is directly attached to the phosphorus atom. As result from this unique substitution pattern, the thus designed ligands depict significantly diminished donor properties if compared with their neutral counterparts. Thus, if in a hypothetical catalytic cycle, the step that determines the rate is facilitated by an increase of the electrophilicity at the metal center; then, the use of α-cationic ancillary phosphines can be highly beneficial. This fact, combined with their easy syntheses and stability, which allows an easy handling, make α-cationic phosphines a useful tool for the synthetic practitioner. Our research on the topic demonstrates that generally a remarkable ligand acceleration effect is observed when α-cationic phosphines are employed in Au(I)- and Pt(II)-promoted cycloisomerizations; moreover, in some cases even otherwise not operative transformations can be promoted. This Account describes how we entered into the topic, our efforts, and those of others to understand the coordination behavior of α-cationic phosphines and further develop their range of applications in catalysis; but it also identifies the drawbacks associated with their use, which limit their range of application.1 Introduction2 Polycationic Phosphines: Stronger Acceptors than Phosphites3 Inconveniences Derived from the Use of (Poly)cationic phosphines4 A Second Generation of Cationic Ligands: α-Pyridiniophosphines5 Chiral α-Cationic Phosphines6 α-Radical Phosphines and (Poly)cationic Phosphine Oxides7 Conclusions and Outlook
Keywords: α-cationic phosphines; ligand design; π-acid catalysis; hydroarylation; asymmetric catalysis; helicenes